Implementation in Management of Education Using ADDIE Method as a Foreign Language Teachers to Improve Students Language Skill Era 5.0 - Husaini, Husaini (Humanitatis : Journal of Language and Literature, 2024)
Implementing learning by utilizing digital can be a solution for foreign language teachers in the era of Society 5.0 to improve students’ language skills at school, especially with the implementation of the independent learning curriculum; students are expected to be more active, creative, and innovative in class. However, problems often occur with students’ foreign language skills in its implementation. This happens because of various obstacles, including teachers who still use the lecture method in learning, so students’ interests and understanding are small. This is caused by presenting material that does not attract students’ interest. This research used a qualitative descriptive method and developed the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. This research aims to determine learning methods using ADDIE-based learning, as well as the effectiveness of their use in foreign language learning. The research results show that: 1) The design of the ADDIE model was carried out as follows: a. analysis stage, b. material, strategy, and media design stage, c. development stage, d. implementation design stage in e-learning learning situations and e. trial and error validation by experts, 2) The results of the validity of the learning planning design based on the material validator obtained good results, namely with a score of 70% with good criteria and the media validator obtained 80% results in the very good category, and 3) The results of student responses with very good answers on media design reached 88%. So, this method is very useful for students in improving their foreign language skills.